Effective Stress and Compressibility of Unsaturated Clayey Soil under Drying and Wetting Cycles - Kholghifard, Mehrdad (Periodica Polytechnica Civil Engineering, 2020)
Naturally, soil moisture reduces during dry seasons when the soil is in drying state; while it increases during wet seasons when the soil is in wetting state. Previous studies have shown that for an unsaturated soil sample, soil-water characteristic curves (SWCCs) do not match in wetting and drying paths. The differences between wetting and drying paths are called the hydraulic hysteresis. The hydraulic hysteresis plays an important role in mechanical properties of soil such as shear strength, volume change, and settlement. The objective of this research is to study the effects of drying and wetting on the effective stress and compressibility of unsaturated clayey fine-grained soils. To this end, saturated and unsaturated triaxial tests were performed on the soil samples under various normal mean stresses, and matrix suctions in drying and wetting paths. It was found that soil samples bear higher levels of effective stress in the drying path than the wetting path under a same level of suction. The attained values of effective stress parameter (χ) showed that the Bishop’s effective stress parameter (χ = Sr) is not properly applicable for the clayey soil. Moreover, the resulting loading-collapse curve (LC) revealed that the effective pre-consolidation pressure in the drying and wetting stages changed even with same degrees of matrix suction.